The Implementation Of Scientific Approach In TeachingEnglish Of 8th Grade At SMP Muhammadiyah 7 Surakarta In 2014/2015 Academic Year: A Naturalistic Study - Hapsari, Bety Dwi; , Prof. Dr. Endang Fauziati, M. Hum; , Aryati Prasetyarini, S.Pd, M.Pd (2015)
This research aims to describe the implementation of scientific approach in teaching English of 8th grade at SMP Muhammadiyah 7 Surakarta. It was done to know learning objective, instructional material, classroom procedure, classroom technique, teaching media, teacher roles and learner roles of implementation of scientific approach in teaching English of 8th grade at SMP Muhammadiyah 7 Surakarta. The type of this research is descriptive qualitative research. The writer gets the data from event, informant and document. The techniques of collecting data are observation, interview and documentation. The procedures of analyzing data are reduction of the data, display and verification. The results of this research show that 1) there are two learning objectives namely, general and specific learning objective, 2) the teachers used two kind of instructional material namely, printed material and unprinted material, 3) the classroom procedure used by the teachers is 5M namely, Observing, Questioning, Experimenting, Associating and Communicating that consists of two patterns, 4) English teachers used some techniques based on learning cycle (5M) such as Reading a Passage, Role Playing, Prediction, Discussion, Problem Solving, Skimming and Scanning, Listing, Oral Repetition, Brainstorming, Answering question, 5) Teaching media used by the teachers namely, pictures and images, LCD, laptop and video, 6) the teacher has some roles such as, teacher as planner, as manager, as facilitator, and as motivator, 7) the students has some roles namely, learners monitor and evaluate their own progress, learner learn from the teacher and learner are members of a group and learn by interacting with others. The implementation of scientific approach in teaching English of 8th grade students of SMP Muhammadiyah 7 Surakarta was not fully complete.